Diseñar un complejo de equinoterapia para rehabilitación física de personas con discapacidad, cantón Paján, provincia Manabí - Suárez Pico, Alex Santiago (2021)
This thesis project is focused on evaluating the deficiencies in this sector and to help lowincome people in the Paján Canton, an attempt is made to make a design and facilitate the needs of people with disabilities, because they have to travel to other provinces to carry out their physical treatment, this favors the Cantón Paján. Design an Equine Therapy Complex for Physical Rehabilitation of People with Disabilities, Cantón Paján, and Manabí Province. It is to collaborate with information from a general, didactic and beneficial point of view in said population, for this it will include all kinds of specialists such as Psychology, Neurology, Physical Therapies, Language Therapies, etc……..